Tin Exploration in Offshore of West Karimun-Kundur Island - Nasir Umar; Armeyn Simatupang; Ichwan Azwardi (Berita Sedimentologi, 2000)
Karimun-kundur islands are located in Riau archipelago as a part of a tin belt which extends from Myanmar in the north through Malaysia, Singkep, Bangka, and Belitung island in the southern end. The Karimun-kundur islands are also a part of granite island chain that emerged within the tin belt. The dating from the granite indicates Upper Triassic age and since then a lot of tectonic activities have taken place creating large variation of structural features which then influence the deposition of Quaternary tin deposit. The tectonism was intensively occurred in Pre-Tertiary time which was predominated by compression due to subduction processes. This structuring later control the younger structures within the study area.In Western Kundur (Lalang island area), there are some small granite islands that act as the sedimentary source rock. Structural reconstruction of the pattern of these islands show plausible structural orientation which is also aligned with the bathymetry. The water depth tends to be deeper in the northern portion which indicates that the Lalang island area was previously a paleo high in the past.Geophysical surveys had been undertaken within the study area, such as seismic reflection and magnetic. The seismic data quality was not satisfactory due to shallow surface condition, whereas the magnetic survey provided a better outcome. The most plausible interpretation of the magnetic dataset revealed that the basement was formed by granitoid and metasediments.